Bereavement and imprisonment: prisoners’ experiences of death-related grief - Simanovic, Tia (A Scottish Justice Fellowship Briefing Paper, 2023)
This briefing provides an overview of key messages from doctoral research on prisoners’ experiences of bereavement prior to and/or during imprisonment in two Scottish prisons (Simanovic, 2021). It elaborates on the main findings and situates them into current policy contexts in Scotland, focussing specifically on the unintended consequences of the restrictive, and discretionarily applied, definition of a near relative in the Escorted Day Absence Direction (2011), used for regulating day release(s) for different purposes, including funerals or hospital visits of terminally ill relatives.